Does Intravenous Lactated Ringer’s Solution Raise Serum Lactate? - Zitek, Tony; Skaggs, Zachary D.; Rahbar, Aryan; Patel, Jayme; Khan, Memona (The Journal of emergency medicine, 2018)
Serum lactate increases in states of severe sepsis and shock, but its interpretation may be subject to confounders. Lactated Ringer's solution (LR) is used in the resuscitation of septic patients and contains 28 mmol/L of sodium lactate. We sought to determine if a bolus of 30 mL/kg of LR increases serum lactate levels. In this double-blind, randomized controlled trial, 30 volunteers were assigned to receive either 30 mL/kg of intravenous LR or normal saline (NS). Serum lactate was measured before and after the fluid bolus. The primary outcome was the difference in the change in lactate between the LR and NS groups. Secondarily, we assessed the change in pH, bicarbonate, sodium, and chloride in each group. After 30 mL/kg of intravenous LR, the mean serum lactate level increased by 0.93 mmol/L (95% confidence interval 0.42–1.44 mmol/L). However, there was also a small increase in the mean serum lactate level in the NS group of 0.37 mmol/L (95% confidence interval −0.26 mmol/L to 1.00 mmol/L), such that there was not a statistically significant difference in the change in lactate when comparing the LR group to the NS group (p = 0.2). The NS group saw larger declines in pH and bicarbonate and greater increases in chloride compared with the LR group. In healthy individuals, a modest but significant rise in mean serum lactate was seen after a 30 cc/kg LR bolus. There was no difference in mean serum lactate when comparing a 30 mL/kg bolus of NS to LR.